1998
DOI: 10.1007/s004020050270
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic osteotomies: anatomic pitfalls at the ischium

Abstract: Pelvic osteotomies for acetabular dysplasia include an osteotomy of the ischium. The potential anatomical hazards of three different osteotomies of the ischium were assessed by performing a triple osteotomy in a series of 8 fresh cadaver pelvises. An oblique osteotomy above the sacrospinous ligament using a posterior approach requires that the inferior gluteal and pudendal neurovascular bundles be mobilised and retracted. A transverse osteotomy below the sacrospinous ligament using a posterior approach can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“… 1 Several studies have recognized the PAO's associated risk of neurovascular injury, blood loss and intra-articular fracture associated with doing the procedure without complete exposure. 7 , 10 Through cadaveric training, surgeons have the opportunity to become familiar with the intricate tridimensional nature of the osteotomy, while learning how minimal deviations from the correct technique may compromise the procedure's success. We observed a clear drop in complication incidence as we progressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Several studies have recognized the PAO's associated risk of neurovascular injury, blood loss and intra-articular fracture associated with doing the procedure without complete exposure. 7 , 10 Through cadaveric training, surgeons have the opportunity to become familiar with the intricate tridimensional nature of the osteotomy, while learning how minimal deviations from the correct technique may compromise the procedure's success. We observed a clear drop in complication incidence as we progressed.…”
Section: Discussionmentioning
confidence: 99%
“…From an anterior approach alone, it is impossible to assess the safety of posterior neurovascular structures around the ischium, which are close to the osteotome and therefore at potential risk. 10 Also, C-arm guidance is the only method the surgeon has to avoid medial or lateral deviation of the osteotome. If excessive lateral deviation of the osteotome occurs, the sciatic nerve is at risk and damage to this nerve has been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…de Kleuver et al [6] reported that periacetabular osteotomy is associated with a higher risk of damage to neurovascular structures than is triple osteotomy, because of the reduced visibility for the surgeon and the additional difficulty in accurate orientation. Direct haemostasis is almost impossible and an endovascular embolism is inevitable if the obturator artery is injured during surgery [2,14].…”
Section: Discussionmentioning
confidence: 99%
“…The obturator vein can also be replaced by an enlarged pubic vein, which joins the external iliac vein. In general terms, it can be said that the corona mortis consists of an anastomotic branch between the external iliac or inferior epigastric vessels and the obturator artery or vein, or any vascular connection between the obturator and the external iliac systems in general . The incidence of a venous corona mortis ranges from 27 to 100% in one study, while that of its arterial counterpart from 14.8 to 36% .…”
Section: Introductionmentioning
confidence: 99%